2021
DOI: 10.30918/aerj.93.21.102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reciprocal teaching on the perceived reading comprehension self-efficacy of 2nd-grade pupils: Reflections of the pupils and their teacher

Abstract: This study examined the effects of reciprocal teaching on the perceived reading comprehension self-efficacy of 2nd-grade pupils. The study was designed in pre-post test experimental design with a control group. Qualitative data was also collected from the intervention group students and the classroom teacher who carried out the intervention lessons. Participants consist of typically developing 2nd-grade pupils from a state primary school (n = 34) in Turkey. While the intervention group used a total of 36 lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, a student with high self-efficacy beliefs in the process of reading comprehension can first clearly identify the purpose of reading and carry out its purposeful planning in an environment of effort and achievement-oriented confidence (Altunkaya, 2018).Although perceptions of selfefficacy are not a new concept, it is only recently that studies linking it to reading comprehension have entered the literature in our country (Altunkaya, 2018;Epçaçan, 2013;Eyüp & Uzuner, 2016;İnnalı & Aydın, 2014;Ülper & Şirin, 2018). Moreover, some of the studies on the subject have been carried out on scale adaptation or scale development (Epçaçan & Demirel, 2011;Kula & Budak, 2020;Kula, 2021). On the other hand, when we look at the studies in the field of reading motivation, there are numerous studies in the literature examining its relationship with reading comprehension (Aktaş & Çankal, 2019;Baki, 2019;Batmaz & Erdoğan, 2019;Kızgın & Baştuğ, 2020;Özerbaş & Öztürk, 2017) and the relationship between reading motivation and other factors (Duran & Sezgin, 2012;Gök, 2019;Katrancı, 2015;Öztürk & Aydemir, 2012;Ülper, 2011;Yamaç & Çeliktürk Sezgin, 2018;Yıldız & Akyol, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a student with high self-efficacy beliefs in the process of reading comprehension can first clearly identify the purpose of reading and carry out its purposeful planning in an environment of effort and achievement-oriented confidence (Altunkaya, 2018).Although perceptions of selfefficacy are not a new concept, it is only recently that studies linking it to reading comprehension have entered the literature in our country (Altunkaya, 2018;Epçaçan, 2013;Eyüp & Uzuner, 2016;İnnalı & Aydın, 2014;Ülper & Şirin, 2018). Moreover, some of the studies on the subject have been carried out on scale adaptation or scale development (Epçaçan & Demirel, 2011;Kula & Budak, 2020;Kula, 2021). On the other hand, when we look at the studies in the field of reading motivation, there are numerous studies in the literature examining its relationship with reading comprehension (Aktaş & Çankal, 2019;Baki, 2019;Batmaz & Erdoğan, 2019;Kızgın & Baştuğ, 2020;Özerbaş & Öztürk, 2017) and the relationship between reading motivation and other factors (Duran & Sezgin, 2012;Gök, 2019;Katrancı, 2015;Öztürk & Aydemir, 2012;Ülper, 2011;Yamaç & Çeliktürk Sezgin, 2018;Yıldız & Akyol, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lots of research on language teachers and students have been using various method and approach for listening to develop students' oral skill with reciprocal teaching are rarely found but in reading (KoŞar & Akbana, 2021), (Kula, 2021), (Lenchuk, 2020), (Oo et al, 2021) and (Rojabi, 2021). The results demonstrated in this work provide a new perspective on reciprocal listening while every research always related it to reading comprehension such as in effectiveness of the reflection-based reciprocal teaching (RBRT) by (Oo et al, 2021) for Myanmar upper secondary school students' reading comprehension in English, also a systematic review of prospective observational studies found that reciprocal strategy emphasized positive effect for reading on Turkey Students (Kula, 2021) and how "reciprocal teaching strategies" could help low-proficiency Sixth-Form students improve their reading comprehension (Choo et al, 2011). These arguments are consistent with the findings of (M. Ahmadi & Pourhosein Gilakjani, 2012) and more divisions of methodology are closely affiliated and have common for Jordan students also by (Freihat & Almakhzoomi, 2012).…”
Section: Resultsmentioning
confidence: 99%